(untitled) (Eurasian Scientific Herald, 2022)
This article provides a theoretical analysis of the current state of the problem of preparing engineers for professional activities in the context of cloud technologies. In addition, the features of multi-stage preparation of teaching staff for professional activities using cloud technologies in the conditions of digital education and problems in their implementation are presente